Prevalence and determinants of suicidal ideation among South African Health Sciences students at the onset of the COVID-19 pandemic - Seedat, Samhaa; Sengwayo, Muhle; Gani, Salma; Mashego, Lesedi; Ochayon, Jordan; Shepard, Ashleigh; Vergie, Caleb; Masango, Mxolisi; Makuapane, Lerato P.; Wagner, Fezile; Wagner, Ryan G. (Frontiers in Psychiatry, 2025)
BackgroundSuicidal ideation is an important mental health concern amongst university students who are exposed to multiple stressors. Furthermore, those studying towards degrees in the field of Health Sciences are exposed to additional and unique stressors. This quantitative cross-sectional study aimed to define the prevalence of suicidal ideation and its determinants amongst undergraduate students within the Faculty of Health Sciences at a large, urban South African University.Materials and methodsAn online questionnaire was administered to the 4089 students registered in the Faculty of Health Sciences, with 1211 students submitting responses between March and April 2020. The distribution of this survey coincided with the onset of the national lockdown due to the Covid-19 pandemic. The survey was comprised of validated tools measuring depression (with an included indicator of suicidal ideation), anxiety and resilience. Data analysis was completed using the STATA statistical software (version 14). Both a bivariate analysis and a multivariate logistic regression adjusted for gender were performed.ResultsThe total prevalence of suicidal ideation adjusted for gender and race in this sample was found to be 21.8% (CI: 18.6-25.3; p<0.001). Females had significantly higher suicidal ideation than males (24.1% versus 17.8%; p=0.011). In the multivariate model adjusted for gender, having depressive (aOR 10.8; CI: 7.9-14.8; p<0.001) or anxiety (aOR 5.1: CI: 3.8-6.8; P<0.001) symptoms, only sometimes (aOR 2.7: CI 1.8-4.0; p<0.001) or never (aOR 2.7; CI: 1.8-4.0; p<0.001) having anyone to talk to and being of colored race (aOR 2.0; CI: 1.1-3.4; p=0.019) were significantly associated with suicidal ideation, whilst higher resilience (aOR 0.3; CI: 0.3-0.4; p<0.001) was associated with lower levels of suicidal ideation.ConclusionThe prevalence of suicidal ideation found in this study was higher than that found in the general South African adult population and highlights the need to further investigate and address student mental health, especially students in the field of Health Sciences. Interventions aimed at mitigating the determinants, including depression and anxiety, and promoting the development of protective factors such as resilience and social support may lead to a reduction in suicidal ideation in this population group. Institutional initiatives aimed at improving access to and the quality of mental health services offered to students should be widely advocated for and implemented.